2002
DOI: 10.1007/s00432-001-0309-y
|View full text |Cite
|
Sign up to set email alerts
|

Circadian variation of dihydropyrimidine dehydrogenase mRNA expression in leukocytes and serum cortisol levels in patients with advanced gastrointestinal carcinomas compared to healthy controls

Abstract: In conclusion, our analysis of DPD mRNA expression in leukocytes from healthy controls demonstrates first evidence for a circadian DPD mRNA expression periodicity. In patients with advanced gastrointestinal carcinomas, however, this rhythm seems to be disturbed although circadian endogenous cortisol secretion pattern is maintained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(1 citation statement)
references
References 11 publications
(12 reference statements)
0
1
0
Order By: Relevance
“… 16 Several reports indicated that DPD enzyme activity is partly determined by circadian rhythm, 20 although this circadian expression seems to be abolished in patients with gastrointestinal carcinomas. 21 In addition, it is not unlikely that comedication can influence the expression of DPD enzyme. Studies have indicated that oxaliplatin (an often used anticancer agent) results in a reduced DPD activity.…”
Section: Discussionmentioning
confidence: 99%
“… 16 Several reports indicated that DPD enzyme activity is partly determined by circadian rhythm, 20 although this circadian expression seems to be abolished in patients with gastrointestinal carcinomas. 21 In addition, it is not unlikely that comedication can influence the expression of DPD enzyme. Studies have indicated that oxaliplatin (an often used anticancer agent) results in a reduced DPD activity.…”
Section: Discussionmentioning
confidence: 99%